Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja Pegawai pada Dinas Energi dan Sumber Daya Mineral Provinsi Kalimantan Timur - Amanda Andriana Putri; Rinda Sandayani Karhab; Vera Anitra (BADAN PENERBIT STIEPARI PRESS, 2025)
This research aims to analyze the influence of transformational leadership and organizational culture on employee performance at the Department of Energy and Mineral Resources (ESDM) of East Kalimantan Province. The background of this research is based on the importance of the ESDM Department's role in the sustainable management of natural resources, as well as the challenges faced in improving employee performance. This research uses a quantitative approach with a survey method (Questionnaire). Data was collected through questionnaires distributed to 68 employees of the ESDM Department of East Kalimantan Province. Data analysis techniques include validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis. The research results show that transformational leadership and organizational culture have a positive and significant effect on employee performance. The coefficient of determination (R²) of 0.162 indicates that 16.2% of the variation in employee performance can be explained by these two variables. This research concludes that improving transformational leadership and organizational culture can enhance employee performance at the ESDM Department of East Kalimantan Province. This research has limitations in the use of quantitative methods only, a sample limited to one agency, and limited independent variables. Suggestions for further research include using a mixed-methods approach (quantitative and qualitative), expanding the sample to other agencies, and adding other relevant independent variables.